Syndromes associated with Robin sequence: a national prospective cohort study. Issue 1 (14th November 2022) - Davies, Alex; Davies, Amy; Wren, Yvonne; Deacon, Scott; Cobb, Alistair; McLean, Neil; David, David; Chummun, Shaheel
Abstract : Objectives: To determine the prevalence of syndromic Robin sequence (RS) in the UK and if this group of patients had an increased need for airway and feeding management compared with a non-syndromic RS cohort. Design: A prospective national multicentre study of cases submitted to the Cleft Collective cohort studies. Setting: Specialist cleft services in the UK. Patients: 259 participants who fulfilled the diagnosis of RS. This group was compared with 548 participants with cleft palate only (CPO). Main outcome measures: The primary outcome measure was the presence of a syndrome in patients with RS and CPO. Secondary outcome measures included the use of airway and feeding adjuncts. Results: An associated syndrome was seen in 28% of patients with RS and 14% of patients with CPO. The most common syndrome for the RS group was Stickler syndrome (27%). Syndromic status was significantly higher among patients with RS compared with those with CPO (OR 2.36, 95% CI 1.65 to 3.39; p<0.001). Patients with syndromic RS have an increased reliance on airway adjuncts compared with the patients without syndromic RS (OR 2.02, 95% CI 1.13 to 3.64; p=0.018). There was no evidence of a difference in the use of feeding adjuncts between syndromic and non-syndromic RS groups (OR 2.43, 95% CI 0.78 to 7.58; p=0.126). Conclusion: The presence of a syndrome has implications for management of patients with RS. Early identification of a syndrome may help prevent the consequences of a missed syndromic diagnosis. Routine ophthalmological and genetic screening for Stickler syndrome should be mandatory for all patients with RS.